PENGARUH AUDIT OPERASIONAL DAN PENGENDALIAN INTERN TERHADAP KINERJA PERUSAHAAN (Studi Kasus Pada UD. Cipta Karya Abadi Lamongan) - Nikita Nitri Pratiwi; Novi Darmayanti (Fakultas Ekonomi, 2023)
In achieving good corporate performance, the business environment needs to establish a division that focuses on monitoring with the aim of adding value so as to improve company operations. This research was conducted to determine the effect of operational audit and internal control on company performance. This research was conducted at UD. Cipta Karya Abadi in Lamongan Regency. The sample was taken based on the Nonprobability Sampling technique, the number of respondents in this study was 38 employees. Data were collected by distributing questionnaires directly to each employee, the method used was multiple linear regression analysis. The results of this study indicate that the operational audit and internal control simultaneously have a positive and significant effect on the company's performance, the operational audit partially has a positive and significant effect on the company's performance, while the internal control partially has no significant effect on the company's performance.